2021
DOI: 10.1021/acs.est.1c04176
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Mortality and Fine Particulate Air Pollution by Species and Source in a National U.S. Cohort

Abstract: The purpose of this study was to estimate cardiopulmonary mortality associations for long-term exposure to PM2.5 species and sources (i.e., components) within the U.S. National Health Interview Survey cohort. Exposures were estimated through a chemical transport model for six species (i.e., elemental carbon (EC), primary organic aerosols (POA), secondary organic aerosols (SOA), sulfate (SO4), ammonium (NH4), nitrate (NO3)) and five sources of PM2.5 (i.e., vehicles, electricity-generating units (EGU), non-EGU i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
(67 reference statements)
2
14
0
Order By: Relevance
“…As a result, policy makers and regulators have developed PM 2.5 exposure guidelines based on epidemiological estimates of disease burdens from unspeciated PM 2.5 . However, recent work has indicated that PM 2.5 toxicity might vary significantly by aerosol composition and source. More research is thus urgently required to estimate the speciated health burdens of PM 2.5 to accurately inform the next generation of exposure guidelines. The modeled heterogeneity in global PM 2.5 composition in this study indicates that estimates of human health impacts that do not consider PM 2.5 composition may be in considerable error, especially in understudied regions (or under future emission regimes).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, policy makers and regulators have developed PM 2.5 exposure guidelines based on epidemiological estimates of disease burdens from unspeciated PM 2.5 . However, recent work has indicated that PM 2.5 toxicity might vary significantly by aerosol composition and source. More research is thus urgently required to estimate the speciated health burdens of PM 2.5 to accurately inform the next generation of exposure guidelines. The modeled heterogeneity in global PM 2.5 composition in this study indicates that estimates of human health impacts that do not consider PM 2.5 composition may be in considerable error, especially in understudied regions (or under future emission regimes).…”
Section: Resultsmentioning
confidence: 99%
“…Particulate matter (PM) is one of the most critical pollutants in the atmosphere, as it has been found to be associated with increased human morbidity and mortality, mainly related to cardio-respiratory diseases [1][2][3]. Although the specific mechanisms of PM-induced health effects are still largely unknown, there is increasing consensus that they involve oxidative stress through the generation of excessive reactive oxygen species (ROS) and/or inadequate antioxidant defenses [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work indicates that preferentially controlling emissions of ROC could yield significant health benefits by mitigating the mortality associated with ambient air pollution in the U.S. (Pye et al, 2022). These benefits come primarily from reductions in SOA which is strongly associated with cardiorespiratory mortality (Pye et al, 2021;Pond et al, 2022). ROC also includes hazardous air pollutants (HAPs) such as benzene and formaldehyde that result in cancer and noncancer risks to health (Scheffe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%